The implementation of consciousness-raising technique on grammar teaching to a class of second-year non-major students at Hanoi National University of Education: a case study - Tạ, Thanh Bình (ĐHNN, 2017)
Chapter 1, the Literature Review, offers the theoretical background to this study by reviewing different approaches to grammar teaching and discussing a number of studies on learners’ preferences and effectiveness of grammatical consciousness-raising. Chapter 2, the Methodology, reports the design of the study, the subjects, the data collection instruments used for this study and the statistical method to analyze the data. Chapter 3, the Findings and Discussion, provides an analysis of the data, the interpretation of the results and discusses some prominent issues arising from the study results.